Effects of Different Photoperiods on Peripheral 5-Hydroxytryptamine Metabolism, Breast Muscle Glucose Metabolism, and Myopathies in Broilers - Miao Yu; Mengjie Xu; Guangju Wang; Jinghai Feng; Minhong Zhang (Metabolites)
Background: There is a close relationship between breast muscle glucose metabolism, peripheral 5-hydroxytryptamine (5-HT), and myopathies in animals. Here, this study aimed to investigate the effects of different photoperiods on peripheral 5-HT metabolism, white striping (WS), and wooden breast (WB) in broilers. Methods: A total of 216 healthy 5-day-old (d) Arbor Acres (AA) male broilers were randomly assigned to 12L:12D, 18L:6D, and 24L:0D photoperiods for 4 weeks. Results: Compared with the 12L:12D photoperiod, we found the WB score in broilers was significantly increased in the 18L:6D and 24L:0D photoperiod at week 4 (p < 0.05). Muscle glycogen was significantly reduced (p < 0.05) and glycolysis was promoted in the breast muscles of broilers under the 18L:6D and 24L:0D photoperiods at week 2 and 4. Peripheral 5-HT concentrations, the mRNA expression of tryptophan hydroxylase 1 (TPH1) and serotonin transporter (SERT) in the cecal mucosa, and 5-hydroxytryptamine receptor 2A (5-HTR2A) mRNA expression in the breast muscle of broilers significantly up-regulated in the 18L:6D and 24L:0D photoperiod at week 2 and 4 (p < 0.05). Conclusions: Our findings revealed that extending the photoperiod improved the breast muscle growth rate, but up-regulated 5-HT synthesis and secretion to higher peripheral 5-HT, induced breast muscle glucose metabolism disorder, and increased WB incidence rates in broilers.